Cesarean scar pregnancy report of two cases from Syria - Salman, Safa K. (International Journal of Scientific Reports, 2026)
Notably there is a rapidly rate increase of caesarean deliveries, for nonmedical reasons, in Syria. Globally, cesarean sections (CS) outnumber vaginal deliveries according to World Health Organization (WHO), it was also noticed an increase of maternal complications, including a new kind of ectopic pregnancy in the CS scar. This report presents two cases of caesarean scar pregnancies in Syria. 42 years old patient G7P4, previous 3 CS, presented with pregnancy, a cesarean scar implantation was detected, and she refused the termination of the pregnancy. At ten gestational weeks came complaining of vaginal bleeding, due to fetal death, failed dilation and curettage (D&C). Then hysterectomy has been performed. The second case is a 38 years old patient, with failed D&C by a diagnosed cesarean scar pregnancy, previous 3 CS with vaginal bleeding, the patient requested the hysterectomy and that has been done. In these two cases, the total hysterectomy was a good method of management.